A societal transition of MSW management in Xiamen (China) toward a circular economy through integrated waste recycling and technological digitization. (15th May 2021) - Kurniawan, Tonni Agustiono; Lo, Waihung; Singh, Deepak; Othman, Mohd Hafiz Dzarfan; Avtar, Ram; Hwang, Goh Hui; Albadarin, Ahmad B.; Kern, Axel Olaf; Shirazian, Saeed
Abstract: Recently Xiamen (China) has encountered various challenges of municipal solid waste management (MSWM) such as lack of a complete garbage sorting and recycling system, the absence of waste segregation between organic and dry waste at source, and a shortage of complete and clear information about the MSW generated. This article critically analyzes the existing bottlenecks in its waste management system and discusses the way forward for the city to enhance its MSWM by drawing lessons from Hong Kong's effectiveness in dealing with the same problems over the past decades. Solutions to the MSWM problem are not only limited to technological options, but also integrate environmental, legal, and institutional perspectives. The solutions include (1) enhancing source separation and improving recycling system; (2) improving the legislation system of the MSWM; (3) improvement of terminal disposal facilities in the city; (4) incorporating digitization into MSWM; and (5) establishing standards and definitions for recycled products and/or recyclable materials. We also evaluate and compare different aspects of MSWM in Xiamen and Hong Kong SAR (special administrative region) under the framework of 'One Country, Two Systems' concerning environmental policies, generation, composition, characteristics, treatment, and disposal of their MSW. The nexus of society, economics of the MSW, and the environment in the sustainability sphere are established by promoting local recycling industries and the standardization of recycled products and/or recyclable materials. The roles of digitization technologies in the 4 th Industrial Revolution for waste reduction in the framework of circular economy (CE) are also elaborated. This technological solution may improve the city's MSWM in terms of public participation in MSW separation through reduction, recycle, reuse, recovery, and repair (5Rs) schemes. To meet top-down policy goals such as a 35% recycling rate for the generated waste by 2030, incorporating digitization into the MSWM provides the city with technology-driven waste solutions. Graphical abstract: Image 1 Highlights: Hong Kong's effectiveness in tackling MSW is a source of inspiration for Xiamen. Public participation and their environmental awareness are important for sound MSWM. Standardization of recycled products promotes recycling industry in Xiamen. Incorporation of digitization enhances public participation in waste reduction. Digitization technology is critical for waste recycling industry.